2002
DOI: 10.1093/brain/awf175
|View full text |Cite
|
Sign up to set email alerts
|

Focal cortical dysplasia: neuropathological subtypes, EEG, neuroimaging and surgical outcome

Abstract: Since the original description by Taylor, the term focal cortical dysplasia has been used to refer to a wide range of alterations of the cortical mantle. More recently, these conditions have been described from neuroimaging, neuropathological and genetic standpoints, generating several classifications. It is widely recognized that these classifications are unsatisfactory. We propose a simplified classification of focal cortical dysplasias based on easily recognized neuropathological characteristics. We retrosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

44
489
6
27

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 597 publications
(576 citation statements)
references
References 47 publications
44
489
6
27
Order By: Relevance
“…For instance, a synchronous GABA A receptormediated event appears to be able to initiate ictal discharges in post-surgical neocortical tissue removed from patients with Taylor type focal cortical dysplasia (Avoli et al, 1999;D'Antuono et al, 2004); it was shown in these experiments that, as reported in rodent limbic structures, this synchronous GABAergic potential is accompanied by a transient increase in [K + ] o as well as that the ictal activity is abolished by GABA A receptor antagonists or μ-opioid receptor agonism. Interestingly, it has been reported that the dysplastic tissue resected from these patients presents with decreased number of presumptive interneurons that, however, provide increased GABAergic innervation to principal cells (Spreafico et al, 1998;Tassi et al, 2002). In addition, Alonso-Nanclares et al (2005) have reported that giant ectopic neurons in the white matter are surrounded by hypertrophic basket formations.…”
Section: Gaba a Receptor-mediated Inhibition May Implement Epileptifomentioning
confidence: 97%
“…For instance, a synchronous GABA A receptormediated event appears to be able to initiate ictal discharges in post-surgical neocortical tissue removed from patients with Taylor type focal cortical dysplasia (Avoli et al, 1999;D'Antuono et al, 2004); it was shown in these experiments that, as reported in rodent limbic structures, this synchronous GABAergic potential is accompanied by a transient increase in [K + ] o as well as that the ictal activity is abolished by GABA A receptor antagonists or μ-opioid receptor agonism. Interestingly, it has been reported that the dysplastic tissue resected from these patients presents with decreased number of presumptive interneurons that, however, provide increased GABAergic innervation to principal cells (Spreafico et al, 1998;Tassi et al, 2002). In addition, Alonso-Nanclares et al (2005) have reported that giant ectopic neurons in the white matter are surrounded by hypertrophic basket formations.…”
Section: Gaba a Receptor-mediated Inhibition May Implement Epileptifomentioning
confidence: 97%
“…Since the first description of the neuropathologic features of FCD provided by Taylor et al in 1971 [95], different FCD classification systems have been proposed [93,94,[96][97][98]. A task force of the Diagnostic Methods Commission of the International League Against Epilepsy (ILAE) has recently generated a new consensus classification of distinct FCD subtypes based on histopathological features [6].…”
Section: Clinical and Neuropathologic Featuresmentioning
confidence: 99%
“…12 Estas duas formas foram melhor caracterizadas do ponto de vista clínico, neuropsicológico e especialmente de imagem, permitindo, frequentemente, uma antecipação diagnóstica in vivo das anormalidades histológicas. 13 No outro extremo estão as epilepsias causadas por lesões não desenvolvimentais. A lista de lesões epileptogênicas não desenvolvimentais é extensa e as mais comuns são a ulegiria atrófica ou cicatriz porencefálica, resultantes de insulto hipóxico-isquêmico prévio, esclerose temporal mesial, tumores não-desenvolvimentais e lesões vasculares, incluindo Síndrome de Sturge Weber, além de lesões resultantes de infecções congênitas ou adquiridas.…”
Section: Epilepsia Na Infânciaunclassified
“…59 As descargas parecem ser o resultado de interações complexas entre a heterotopia e o neocórtex e estudos utilizando EEG intracranial demonstraram que a substância cinzenta heterotópica é capaz de gerar atividade elétrica usualmente sincronizada mas também independente do córtex adjacente. 13,59,60 Embora os mecanismos exatos pelos quais as crises causem alterações na arquitetura do sono não sejam totalmente compreendidos é provável que desequilíbrios neuropatológicos, como os encontrados nas malformações corticais, como perda ou desorganização celular, sejam a base para os transtornos do sono associados à epilepsia. 61 …”
Section: Microestrutura Do Sono E Epilepsiasunclassified